Three-dimensional finite element analysis of anterior single implant-supported prostheses with different bone anchorages - Verri, Fellippo Ramos [UNESP]; Santiago Júnior, Joel Ferreira; Almeida, Daniel Augusto de Faria [UNESP]; Verri, Ana Caroline Gonçales [UNESP]; Batista, Victor Eduardo de Souza [UNESP]; Lemos, Cleidiel Aparecido Araujo [UNESP]; Noritomi, Pedro Yoshito; Pellizzer, Eduardo Piza [UNESP] (Wiley, 2015)
The aim of this study was to evaluate the stress distribution of monocortical and bicortical implant placement of external hexagon connection in the anterior region of the maxilla by 3D finite element analysis (FEA). 3D models were simulated to represent a bone block of anterior region of the maxilla containing an implant (4.0 × 10.0 mm) and an implant-supported cemented metalloceramic crown of the central incisor. Different techniques were tested (monocortical, bicortical, and bicortical associated with nasal floor elevation). FEA was performed in FEMAP/NeiNastran software using loads of 178 N at 0°, 30°, and 60° in relation to implant long axis. The von Mises, maximum principal stress, and displacement maps were plotted for evaluation. Similar stress patterns were observed for all models. Oblique loads increased the stress concentration on fixation screws and in the cervical area of the implants and bone around them. Bicortical technique showed less movement tendency in the implant and its components. Cortical bone of apical region showed increase of stress concentration for bicortical techniques. Within the limitations of this study, oblique loading increased the stress concentrations for all techniques. Moreover, bicortical techniques showed the best biomechanical behavior compared with monocortical technique in the anterior maxillary area.